2012
DOI: 10.1055/s-0032-1329918
|View full text |Cite
|
Sign up to set email alerts
|

A 15-year Experience of Complex Scalp Reconstruction Using Free Tissue Transfer—Analysis of Risk Factors for Complications

Abstract: Prognostic/risk, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
1
31
2
Order By: Relevance
“…Myocutaneous flaps tended to have higher complications than myofascial in this study population. Chao et al [42] , in a study of 48 scalp reconstructions involving concurrent cranioplasty found no difference in postoperative outcomes between myofascial and fasciocutaneous/myocutaneous free flap reconstruction. Uzun et al [47] , when examining 21 free flap reconstructions for cranioplasty coverage, found no difference in postoperative outcomes between fasciocutaneous and myocutaneous free tissue transfer, although the former had the benefits of shorter hospitalization and lower rates of tissue atrophy.…”
Section: Free Tissue Transfer and 3d Modelingmentioning
confidence: 96%
See 2 more Smart Citations
“…Myocutaneous flaps tended to have higher complications than myofascial in this study population. Chao et al [42] , in a study of 48 scalp reconstructions involving concurrent cranioplasty found no difference in postoperative outcomes between myofascial and fasciocutaneous/myocutaneous free flap reconstruction. Uzun et al [47] , when examining 21 free flap reconstructions for cranioplasty coverage, found no difference in postoperative outcomes between fasciocutaneous and myocutaneous free tissue transfer, although the former had the benefits of shorter hospitalization and lower rates of tissue atrophy.…”
Section: Free Tissue Transfer and 3d Modelingmentioning
confidence: 96%
“…The pliability and thickness of the transplanted tissue allow it to contour to the underlying tissue and withstand postoperative radiation with reduced risk of wound healing complications [11] . Success rates of free tissue transfer for cranioplasty coverage have been reported over 95%, with well tolerated coverage and acceptable cosmetic results [41][42][43][44] .…”
Section: Free Tissue Transfer and 3d Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of scalp defects after resection of cutaneous malignancies can be challenging and requires a considerable degree of surgical planning in order to achieve a satisfactory outcome. Previous studies have developed comprehensive reconstructive algorithms to assist with management of these complex cases [ 1 - 3 ], while other studies have focused on approaches specific to patient risk factors and presentation [ 4 , 5 ]. Advances in microsurgery, a more comprehensive understanding of the anatomical blood supply of the scalp, and the advent of new biologic technologies have all provided the reconstructive surgeon with more tools to combat these defects [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large defects may involve the entire thickness of the soft tissue, or even include calvarial bone and dura mater with cerebrospinal fluid leakage in patients with poor general performance [ 8 , 9 ]. In those cases, chronic soft tissue infection or osteomyelitis often negatively influence the viability of the surrounding tissue and severely limit the use of locoregional flaps for reconstruction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%